Techniczne i technologiczne aspekty zatłaczania wód złożowych do górotworu - Macuda, Jan; Lewkiewicz-Małysa, Aleksandra; Konopka, Elżbieta (My University, 2007)
Reservoir water injection to the rock mass through disposal wells should meet mining and environmental safety requirements. This problem is of special significance in the case of wells that are either abandoned wells or to be closed. The selection criteria for disposal wells and range of necessary tests and analyses of post-exploitation wells' construction designed for injection of reservoir water are presented in the paper. The results of laboratory analyses of reservoir water of known physicochemical properties were used for determining and eliminating original factors favorable to the colmatation of the near-well zone. KEYWORDS: reservoir waters, injection zones, water treatment, sedimentation, flocculation, colmatation, near-well zone.

Zatłaczanie wód złożowych do górotworu poprzez odwierty chłonne powinno być prowadzone przy spełnieniu wymogów dotyczących bezpiecznego prowadzenia prac górniczych i ochrony środowiska. Problem ten ma szczególne znaczenie zwłaszcza przy wykorzystaniu do celów zatłaczaniu odwiertów zastawionych lub przeznaczonych do likwidacji. W artykule przedstawiono kryteria doboru odwiertów chłonnych oraz zakres niezbędnych badań konstrukcji odwiertów poeksploatacyjnych przeznaczonych do zatłaczania wód złożowych do górotworu. Zaprezentowano również wyniki badań laboratoryjnych wód złożowych o znanych właściwościach fizykochemicznych, których celem było określenie i wyeliminowanie pierwotnych czynników sprzyjających kolmatacji strefy przyodwiertowej.
Technical and technological aspects of injection of reservoir water to the rock mass
Wiertnictwo, Nafta, Gaz
Keywords: reservoir waters; injection zones; water treatment; sedimentation; wody złożowe; odwiert chłonny; flocculation; sedymentacja; flokulacja; colmatation; kolmatacja; strefa przyodwiertowa; near-well zone; uzdatnianie wody